Determinants of Service Use Decisions for J&T Express Users in Padangsidimpuan City - Safitri Nasution, Adek; Ardilla Safitri, Riski; Saleh, Idris; Hardana, Ali; Simamora, Chanra; Nasution, Elga (Fakultas Ekonomi dan Bisnis Islam, 2025)
In Padangsidimpuan City, many people choose to use the J&T Express expedition service even though there are various other expedition services. Even though J&T Express won the Top Brand Award in the expedition service category, this service faced many user complaints, with fluctuating transactions and service quality that was considered poor. This research aims to analyze the influence of brand image and service quality on decisions to use J&T Express services, both partially and simultaneously. This research uses a quantitative approach, by collecting primary data through questionnaires to 97 respondents. Data were analyzed using validity, reliability, classical assumptions, multiple linear regression and hypothesis testing with SPSS version 23. The results show that brand image and service quality have a significant influence on the decision to use services, both partially and simultaneously, with an influence contribution of 41. 9%, while 58.1% was influenced by other variables not studied.